Detecting higher-level similarity patterns in programs. - Basit, Hamid Abdul (Software engineering notes.)
Cloning in software systems is known to create problems during software maintenance. Several techniques have been proposed to detect the same or similar code fragments in software, so-called simple clones. While the knowledge of simple clones is useful, detecting design-level similarities in software could ease maintenance even further, and also help us identify reuse opportunities. We observed that recurring patterns of simple clones - so-called structural clones - often indicate the presence of interesting design-level similarities. An example would be patterns of collaborating classes or components. Finding structural clones that signify potentially useful design information requires efficient techniques to analyze the bulk of simple clone data and making non-trivial inferences based on the abstracted information. In this paper, we describe a practical solution to the problem of detecting some basic, but useful, types of design-level similarities such as groups of highly similar classes or files. First, we detect simple clones by applying conventional token-based techniques. Then we find the patterns of co-occurring clones in different files using the Frequent Itemset Mining (FIM) technique. Finally, we perform file clustering to detect those clusters of highly similar files that are likely to contribute to a design-level similarity pattern. The novelty of our approach is application of data mining techniques to detect design level similarities. Experiments confirmed that our method finds many useful structural clones and scales up to big programs. The paper describes our method for structural clone detection, a prototype tool called Clone Miner that implements the method and experimental results.